A comprehensive study of distributed denial of service attack with the detection techniques - Ibrahim, Husam Hamid (2018)
Today, net related net services are indivisible in our life. Therefore, for the success of certain types of organizations, some sustained simplification of services is essential. However, these service area units were usually hindered by the constant threat from numerous kinds of attacks. One such attack is called a distributed denial of service attack and leads to a problem starting with a temporary delay of the server in order to terminate the service's non-availability. A honeypot may be a kind of lure, but in order to prevent potential attackers from diverting, observing, preventing, and ensuring the ongoing convenience of the service. This study gives insight into the problem with distributed denial-of-service attacks. This researcher provides insight into problems caused by distributed denial of service attacks, simulates several types of attacks, analyzes the results, performs each single simulation, and shows how to prevent distributed denial of service attacks. This project explains recently introduced distributed denial of service (DDoS) and its techniques. DDoS attack method using NS - 2 simulator software. This research provides the results of four experiments related to DDoS attacks in a simulation environment with NS 2. The result of this project shows that the three main factors of DDoS attack are attack time, attack strength and pocket size. Attack time is mainly related to attack strength. Finally, it is shown that the buffer size plays a role in processing attack traffic.